2018
DOI: 10.1007/s12471-018-1192-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging in patients with cardiac implantable electronic devices

Abstract: In recent years the prevalence of implantation of a cardiac implantable electronic device (CIED) has increased due to expanding implantation indications and prolonged life expectancy. Diagnostic strategies increasingly employ magnetic resonance imaging (MRI) to aid therapeutic strategies. In earlier guidelines, MRI was contra-indicated in patients with CIEDs, mainly due to previous reports of severe complications. With the development of MRI-conditional CIEDs and recent evidence concerning non-MRI-conditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…Previously cardiac MRI was thought to be difficult, if not impossible, in the patients with CIED but recent publications have shown that even in the legacy devices the use of MRI is safe 123 . In many of these patients the newer sequences, such as wideband pulse sequence and inversion recovery sequence, were used to reduce artifacts 124,125 .…”
Section: Thoracic Spinal and Cardiac Mri In Patients With Ciedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously cardiac MRI was thought to be difficult, if not impossible, in the patients with CIED but recent publications have shown that even in the legacy devices the use of MRI is safe 123 . In many of these patients the newer sequences, such as wideband pulse sequence and inversion recovery sequence, were used to reduce artifacts 124,125 .…”
Section: Thoracic Spinal and Cardiac Mri In Patients With Ciedsmentioning
confidence: 99%
“…There have been several recent publications suggesting different safety protocols for carrying out an MRI in patients with CIED 11,12,94,123,130,131,134–136 . The overall idea of the protocol is as summarized in Figure 3.…”
Section: Proposed Protocols In Literature For Mri In Patients With Nomentioning
confidence: 99%
“…Da das MRT die empfindlichste bildgebende Methode zur Erkennung perineuraler Tumorausbreitungen (PNTS) ist [2] und da eine Änderung der Empfehlungen für die Bildgebung bei Patienten mit implantierten Herzgeräten eingeführt wurde [3,4], wurde jetzt ein MRT durchgeführt. Es zeigte eine infiltrative Gewebsvermehrung im rechten Jochbein, die in den rechten Ohrmuschelbereich infiltrierte und die Hirnnerven (HN) V und VII in Mitleidenschaft zog (Abbildung 1b, c).…”
unclassified
“…Given that MRI is the most sensitive imaging method for the detection of perineural tumor spread (PNTS) [2], and that a change in recommendations for imaging in patients with cardiac implantable devices has been implemented [3,4], an MRI was performed. It showed an aggressive mass in the right zygomatic bone that infiltrated the right auricular area, affecting both cranial nerves (CN) V and VII (Figure 1b, c).…”
mentioning
confidence: 99%